1998
DOI: 10.1038/sj.ijo.0800571
|View full text |Cite
|
Sign up to set email alerts
|

Liver abnormalities in severely obese subjects: Effect of drastic weight loss after gastroplasty

Abstract: OBJECTIVE: To examine the factors associated with liver steatosis in severely obese subjects and to test the potential reversibility of fatty liver after weight loss. DESIGN: Retrospective clinical study. SUBJECT: 528 obese patients before bariatric surgery and 69 obese subjects of the initial cohort evaluated before and 27 AE 15 months after gastroplasty. MEASUREMENTS: Fatty deposition (scored as mild, moderate or severe) and in¯ammatory changes were evaluated in liver biopsies; clinical (body mass index (BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
258
2
16

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 451 publications
(286 citation statements)
references
References 11 publications
10
258
2
16
Order By: Relevance
“…59 In a large personal series of 528 severely obese subjects (BMI 42.6 + 6.8 kg/m 2 ), 74% of the biopsies showed fatty deposition, estimated as mild in 41% of cases, moderate in 32% and severe in 27%. 60 The severity of steatosis was positively associated with BMI (P = 0.002), but not with the known duration of obesity. 55 Ten percent of these patients had signs of steatohepatitis, inflammatory changes being scored as mild in 86%, moderate in 12% and severe in 2% of cases.…”
Section: The Association Of Nash With Obesitymentioning
confidence: 90%
See 2 more Smart Citations
“…59 In a large personal series of 528 severely obese subjects (BMI 42.6 + 6.8 kg/m 2 ), 74% of the biopsies showed fatty deposition, estimated as mild in 41% of cases, moderate in 32% and severe in 27%. 60 The severity of steatosis was positively associated with BMI (P = 0.002), but not with the known duration of obesity. 55 Ten percent of these patients had signs of steatohepatitis, inflammatory changes being scored as mild in 86%, moderate in 12% and severe in 2% of cases.…”
Section: The Association Of Nash With Obesitymentioning
confidence: 90%
“…60 When compared with patients without fatty liver deposition, those with liver steatosis had significantly higher fasting plasma glucose, insulin, triglycerides and ALT levels. The severity of the steatosis was positively correlated not only with BMI (P = 0.002), but also with fasting plasma glucose, insulin and triglycerides concentrations and serum liver enzyme levels (Figure 1).…”
Section: The Association Of Nash With Insulin Resistance Syndromementioning
confidence: 95%
See 1 more Smart Citation
“…116 Consistent with a larger burden of obesity-related comorbidities in extremely obese adults, liver disease in such patients is more prevalent and advanced. [121][122][123][124][125][126] Therefore, to define the spectrum and determinants of NAFLD in extremely obese adolescents, we correlated liver histology with clinical features and compared findings to reported adult Bariatric surgery for pediatric extreme obesity TH Inge et al data. 127 In our cross-sectional study of 41 adolescent subjects undergoing gastric bypass, 83% had NAFLD.…”
Section: Nafld and Steatohepatitismentioning
confidence: 99%
“…Several studies in adults have reported improvement in NAFLD and NASH after surgery, though some studies have highlighted a transient increase in inflammation after surgery. 34,121 Two recent studies of outcome of NASH after bariatric surgery in adults have demonstrated significant decreases in steatosis, but variable or no changes in inflammation and fibrosis. 128,129 Although both of these recent studies in adults suggest a clear beneficial effect of gastric bypass surgery on NAFLD and NASH, the persistence of fibrosis and inflammation in a subset of patients indicate the need for longer-term followup.…”
Section: Nafld and Steatohepatitismentioning
confidence: 99%